(3MJi Gdjbjfs - (3eMeO, SYGOs ((3GdbGgQIs (3OGQ RMeI cJGH ddfTQ hGdJhRjYs, 2023)
(3ef XdeI Gddjd HRZ fhQ Waja jSQj fMhj, aHOCJ GScf dbOQ Gddg , HOCJ CYj Cf GdhbJ GdeYdhe deG jCJ HYO , GdYjT Ohf age Ch eYQaI CTHg HMjGI HGQOI dG WYe dgG hdG QGFMI jLYdfj cJQS CMeb aj eGcjfI UOFg , dGJYhd Ydjg aj LOjOs
Keywords: (3GdePcQGJ aj GdCOH GdYQHjs; (3bUU hMcGjGJs